Learning Acquisition through The Art of Reading: A Theory - Geryl D. Cataraja (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the challenges on the implementation of SQ3R on the reading comprehension of students and to find out what theory can be generated from the study. The method in this study is a qualitative research design grounded theory model. The Theory on the learning process has been generated and formulated, “Learning can be facilitated through a reading activity if students experience something new or novel activity when they are engaged in tasks especially on mental organizations and interaction among themselves and with the teacher.” The result revealed that SQ3R reading strategy improves students’ learning outcomes it is recommended that Teachers could apply effective strategies in the teaching-learning process to enhance students’ learning outcomes.